Multi-level determinants of vaccination of the American Indian and Alaska Native population: a comprehensive overview - Zhao, Junying; Jaggad, Rashmi; Zhang, Ying; Campbell, Janis E.; Ghosh, Pallab K.; Kennedye, James R.; Ali, Tauqeer (Frontiers in Public Health, 2025)
ContextAmerican Indians and Alaska Natives (AIANs) are historically disadvantaged, losing 20 million (95%) of their population largely through epidemics since 1,520 and continuing lower overall vaccination coverage than other races. Determinants of this lower coverage are underexamined.MethodsAmong peer-reviewed relevant articles since 1968, 39 studied AIANs solely; 47 drew general population samples, including AIANs. We employed rigorous economic definitions and framework of Individual Decision-Making Under Uncertainty. The Social-Ecological model identified determinants and mechanisms at five levels.FindingsIndividual-level determinants include: (1) vaccine-preventable disease (VPD) and vaccine knowledge; (2) vaccine safety, efficacy, moral hazard beliefs; (3) preferences; (4) income and post-subsidy costs. Interpersonal-level determinants include others’ knowledge and preferences. Organizational-level characteristics of Indian Health Service, Tribal, Urban Indian (IHS/T/U) facilities include: (1) supply of vaccine products, providers, services; (2) provider cultural competency, vaccine recommendations, standing orders; (3) patient reminder/recall. Community-level characteristics include: (1) socioeconomics and geographics; (2) information infrastructure; (3) cultural values, practices, languages; (4) historical epidemic knowledge; (5) historical harms thus distrust in government, health system, science. Societal-level determinants include: (1) federal recognition and entitlements; (2) tribal self-determination; (3) state Medicaid enrollment; (4) structural racism.Policy recommendationsTribal interventions may (1) increase AIANs’ knowledge about VPDs, vaccines, Medicaid enrollment; (2) design risk/cost–benefit calculations using scientific objective probabilities of vaccine safety and efficacy; (3) tailor messages to epidemic histories, narratives, values; (4) outreach by trusted messengers. I/T/U organizational interventions may reduce transportation costs while increasing provider supplies, cultural competency, and vaccine standing orders. Federal policies may increase IHS funding, tribal infrastructure, and AIAN data representativeness while eliminating structural racism and generational trauma.ConclusionThis article contributes to literature and practice. It is the first multidisciplinary, comprehensive overview of multi-level determinants and mechanisms of AIAN vaccination. Its findings highlight the gaps and limitations of laws and policies impacting AIAN vaccination. It recommends future research, culturally-appropriate interventions, and policies to close the gap to enhance AIAN vaccination and healing.